Decisional regret and choice of breast reconstruction following mastectomy for breast cancer: A systematic review. Issue 4 (7th December 2017) - Flitcroft, Kathy; Brennan, Meagan; Spillane, Andrew
Abstract: Objective: Women facing mastectomy for breast cancer should have the option of considering whether they would like breast reconstruction (BR), and if so, what type and when. Previous research has demonstrated that some women will come to regret their decision about BR. We aim to summarise the evidence about the prevalence of decisional regret (DR) associated with BR choices and identify factors influencing vulnerability to DR. Methods: A systematic review of the literature reporting BR‐related DR published between January 1994 and February 2017 identified 254 initial search results. Thirteen publications from 12 studies (5672 participants) met the selection criteria and were included in the final review. Each article was allocated a quality score out of 24. Results: Overall, DR levels were reported as low and stable, although direct comparison across studies was limited by inconsistencies in measurement and reporting methods. Estimates of DR scores ranged from 9.3/100 to 5.4/20. All studies identified a relationship between higher levels of DR and an insufficient amount, inadequate quality, or unclear nature of information provided to women prior to undergoing mastectomy. A major determinant of DR was new or recurrent cancer, while psychosocial characteristics including depression, distress, and negative body image increased the likelihood of DR. Conclusion: The available research is yet to provide a clear understanding of the many interrelated issues involved in DR. Given the consensus that presurgical information was inadequate, making standardised educational material more widely available and increasing use of breast care nurses in preoperative patient education roles may be useful.